Plessner's Philosophical Anthropology Perspectives and Prospects - de Mul, Jos (Amsterdam University Press, 2014)
Helmuth Plessner (1892-1985) was one of the founders of philosophical anthropology, and his book The Stages of the Organic and Man, first published in 1928, has inspired generations of philosophers, biologists, social scientists, and humanities scholars. This volume offers the first substantial introduction to Plessner's philosophical anthropology in English, not only setting it in context with such familiar figures as Bergson, Cassirer, and Merleau-Ponty, but also showing Plessner's relevance to contemporary discussions in a wide variety of fields in the humanities and sciences.